Джерела доказів у кримінальних справах про ухилення від сплати податків, зборів, інших обов’язкових платежів - Чигрина, Галина Леонідівна (Національна академія внутрішніх справ України, 2004)
Дисертація присвячена встановленню видів та дослідженню змісту джерел доказів, які використовуються для вирішення справ, порушених за ознаками злочинів, передбачених ст. 212 КК України (ухилення від сплати податків, зборів, інших обов’язкових платежів), на стадіях досудового слідства.

In the dissertation general-theoretical problems of proofs’ establishment and their sources in the criminal procedure have been analysed. Expediency of recognition of the defendant testimonies as proofs’ sources, expert, civil plaintiff (representative of plaintiff) and civil respondent (representative of respondent) has been proved. Necessity of updating the names of such proofs’ sources as "material evidences" and “conclusion of expert” has been grounded. The author has proposed her own definition of such notions as “witness on criminal case” and “testimonies of witness”. The statement that proofs on criminal case are not the data themselves received as a result of operative-search activity, but only documents and material evidences as only subjects (things) and documents are used in the criminal procedure with preservation of their initial form has received its further development. The idea on expediency of fixing the list of investigatory actions in the Procedural Criminal Code of Ukraine which can be carried out before instituting of criminal case has been grounded. Inclusion of such investigatory action as seizure to this list has been proposed.
Keywords: доказ; джерело доказів; показання свідка; показання підозрюваного; показання обвинуваченого; висновок експерта; речовий доказ; документи; протоколи слідчих і судових дій; протоколи з відповідними додатками; складеними уповноваженими органами за результатами оперативно-розшукових заходів; proof; proofs’ source; testimonies of witness; testimonies of the suspected; testimonies of the accused; conclusion of expert; material evidences; documents; reports of investigatory and legal actions; reports with the corresponding appendices made by the authorized bodies by the results of operative - search actions